2018
DOI: 10.1111/all.13660
|View full text |Cite
|
Sign up to set email alerts
|

High levels of butyrate and propionate in early life are associated with protection against atopy

Abstract: BackgroundDietary changes are suggested to play a role in the increasing prevalence of allergic diseases and asthma. Short‐chain fatty acids (SCFAs) are metabolites present in certain foods and are produced by microbes in the gut following fermentation of fibers. SCFAs have been shown to have anti‐inflammatory properties in animal models. Our objective was to investigate the potential role of SCFAs in the prevention of allergy and asthma.MethodsWe analyzed SCFA levels by high‐performance liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
357
4
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 379 publications
(379 citation statements)
references
References 36 publications
8
357
4
10
Order By: Relevance
“…The most known metabolites with demonstrated protective properties in human airway inflammation are SCFAs. Children with high amounts of butyrate and propionate in feces at 1 year of age have significantly less atopic sensitization and are less likely to have asthma between 3 and 6 years (Roduit et al, 2019). Moreover, soluble fiber supplementation has been found to decrease sputum eosinophilia and sputum histone deacetylase 9 gene expression in asthma patients (McLoughlin et al, 2019).…”
Section: Bacteria Are the Largest Microbial Population In The Gut Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The most known metabolites with demonstrated protective properties in human airway inflammation are SCFAs. Children with high amounts of butyrate and propionate in feces at 1 year of age have significantly less atopic sensitization and are less likely to have asthma between 3 and 6 years (Roduit et al, 2019). Moreover, soluble fiber supplementation has been found to decrease sputum eosinophilia and sputum histone deacetylase 9 gene expression in asthma patients (McLoughlin et al, 2019).…”
Section: Bacteria Are the Largest Microbial Population In The Gut Andmentioning
confidence: 99%
“…SCFAs have also been shown to reduce inflammation in both OVA and house dust mite (HDM)-induced airway inflammation models Cait et al, 2018). Moreover, oral application of SCFAs to mice during pregnancy and weaning have protect offspring from allergic lung inflammation, with butyrate in particular potently inducing Tregs in the lungs of offspring (Roduit et al, 2019) (Figure 2).…”
Section: Bacteria Are the Largest Microbial Population In The Gut Andmentioning
confidence: 99%
“…For example, microbiota‐accessible carbohydrates (MAC) are complex carbohydrates found in dietary fibers that contribute to microbial diversity and generation of metabolites, such as short‐chain fatty acids (SCFAs) . SCFAs promote regulatory immune responses, and high SCFA levels early in life are associated with protection from atopic sensitization . In contrast, a high‐fat diet is associated with negative effects on microbiota composition and metabolism.…”
Section: Basic Mechanisms Of Allergic Diseases—key Questionsmentioning
confidence: 99%
“…As the skin microbiome is also influenced by such factors as ethnicity, climate, UV exposure and lifestyle factors, future studies of African AD skin microbiome may yield novel regional variations. It was also noted that a butyrate‐rich diet (enriched in fibre‐rich foods and milk fat) shaped the gut microbiome and reduced AD incidence . A recent study in South African children demonstrated differences in gut microbiome composition between rural children with AD compared with their healthy counterparts …”
Section: Summary Of the Major Issues Concerning Ad In Saamentioning
confidence: 99%